Printed from https://www.webqc.org

Chemical Equations Balanced on 02/06/25

 Equations balanced on the previous day Equations balanced on the next day
Balance the equation of any chemical reaction
B(OH)3(s) + CH3OH(l) = B(OCH3)3(s) + H2O(l) =>
B(OH)3(s) + 3 CH3OH(l) = B(OCH3)3(s) + 3 H2O(l)

Ba(NO3)2(aq) + NaOH(aq) = Ba(OH)2 + Na(NO3) =>
Ba(NO3)2(aq) + 2 NaOH(aq) = Ba(OH)2 + 2 Na(NO3)

Ba(OH)2(s) + HCl(aq) = BaCl2(aq) + H2O(l) =>
Ba(OH)2(s) + 2 HCl(aq) = BaCl2(aq) + 2 H2O(l)

C2H5OH + Ag2O = CH3COOH + Ag + H2O =>
C2H5OH + 2 Ag2O = CH3COOH + 4 Ag + H2O

Fe2(SO4)3 + BaCl2 = BaSO4 + FeCl3 =>
Fe2(SO4)3 + 3 BaCl2 = 3 BaSO4 + 2 FeCl3

Ba(OH)2 + H(NO3) = Ba(NO3)2 + H(OH) =>
Ba(OH)2 + 2 H(NO3) = Ba(NO3)2 + 2 H(OH)

P2O5 + NaCl = NaPO3 + POCl3 =>
2 P2O5 + 3 NaCl = 3 NaPO3 + POCl3

Ba + OH = Ba(OH)2 =>
Ba + 2 OH = Ba(OH)2

HCN + NaOH = NaH + CNOH =>
HCN + NaOH = NaH + CNOH

Zn(s) + HNO3(aq) = Zn(NO3)2(aq) + N2O(g) + H2O(l) =>
4 Zn(s) + 10 HNO3(aq) = 4 Zn(NO3)2(aq) + N2O(g) + 5 H2O(l)

Si + LiOH = SiO2 + Li + H2 =>
Si + 2 LiOH = SiO2 + 2 Li + H2

Na2HPO4 + BaCl = Na2Cl + BaHPO4 =>
Na2HPO4 + BaCl = Na2Cl + BaHPO4

CdS + H2SO4 = CdSO4(s) + H2S =>
CdS + H2SO4 = CdSO4(s) + H2S

SO3 + HCl = SO2 + H2O + Cl =>
SO3 + 2 HCl = SO2 + H2O + 2 Cl

LiOH + CuSO4 = Li2SO4 + Cu(OH)2 =>
2 LiOH + CuSO4 = Li2SO4 + Cu(OH)2

NH4NO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + NH4OH(g) =>
2 NH4NO3(aq) + Ba(OH)2(aq) = Ba(NO3)2(aq) + 2 NH4OH(g)

Cl4S + H2O = H2O3S + HCl =>
Cl4S + 3 H2O = H2O3S + 4 HCl

CuSO4 + KOH = K(SO4) + CuOH =>
CuSO4 + KOH = K(SO4) + CuOH

H3PO4(aq) + Ba(OH)2(aq) = Ba3(PO4)2 + H2O(l) =>
2 H3PO4(aq) + 3 Ba(OH)2(aq) = Ba3(PO4)2 + 6 H2O(l)

C2H4 + Br2 = C2H4Br2 =>
C2H4 + Br2 = C2H4Br2

Cl2 + Cr2O3 + KOH = K2CrO4 + KCl + H2O =>
3 Cl2 + Cr2O3 + 10 KOH = 2 K2CrO4 + 6 KCl + 5 H2O

C2H4 + KMnO4 + H2SO4 = H2CO + MnSO4 + K2SO4 + H2O =>
5 C2H4 + 4 KMnO4 + 6 H2SO4 = 10 H2CO + 4 MnSO4 + 2 K2SO4 + 6 H2O

Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)

Al(OH)3(s) + H2SO4(l) = Al2(SO4)3(s) + H2O(l) =>
2 Al(OH)3(s) + 3 H2SO4(l) = Al2(SO4)3(s) + 6 H2O(l)

H3PO4(aq) + Ca(OH)2(aq) = Ca3(PO4)2(aq) + H2O(l) =>
2 H3PO4(aq) + 3 Ca(OH)2(aq) = Ca3(PO4)2(aq) + 6 H2O(l)

BeSO4 + KCl = BeCl2 + K2SO4 =>
BeSO4 + 2 KCl = BeCl2 + K2SO4

H3PO4(aq) + Ba(OH)2(aq) = Ba3(PO4)2(s) + H2O(l) =>
2 H3PO4(aq) + 3 Ba(OH)2(aq) = Ba3(PO4)2(s) + 6 H2O(l)

HNO3 + BaCl2 + Na2SO3 = BaSO4 + NaCl + NO2 + H2O =>
2 HNO3 + BaCl2 + Na2SO3 = BaSO4 + 2 NaCl + 2 NO2 + H2O

NH4NO3(aq) + Ba(OH)2(aq) = NH4OH(aq) + Ba(NO3)2(aq) =>
2 NH4NO3(aq) + Ba(OH)2(aq) = 2 NH4OH(aq) + Ba(NO3)2(aq)

As + H2O = H2AsO4 + AsH3 =>
3 As + 4 H2O = H2AsO4 + 2 AsH3

Cr(s) + Fe(No3)2(aq) = Fe(s) + Cr(No3)3(aq) =>
2 Cr(s) + 3 Fe(No3)2(aq) = 3 Fe(s) + 2 Cr(No3)3(aq)

HNO3(aq) + CaCO3(s) = Ca(NO3)2(aq) + CO2(g) + H2O(l) =>
2 HNO3(aq) + CaCO3(s) = Ca(NO3)2(aq) + CO2(g) + H2O(l)

Si + F2 = SiF =>
2 Si + F2 = 2 SiF

H2 + C + N = HCN =>
H2 + 2 C + 2 N = 2 HCN

Ba(NO3)2(aq) + NaOH(aq) = Ba(OH)2(s) + NaNO3(aq) =>
Ba(NO3)2(aq) + 2 NaOH(aq) = Ba(OH)2(s) + 2 NaNO3(aq)

H2SO4(aq) + Al(OH)3(aq) = Al2(SO4)3(aq) + H2O(l) =>
3 H2SO4(aq) + 2 Al(OH)3(aq) = Al2(SO4)3(aq) + 6 H2O(l)

NCl + Ag = AgCl + N2 =>
2 NCl + 2 Ag = 2 AgCl + N2

Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)

CCH3CH3 + O2 = CO2 + H2O =>
2 CCH3CH3 + 9 O2 = 6 CO2 + 6 H2O

Br2(l) + KI(aq) = I2(aq) + KBr(aq) =>
Br2(l) + 2 KI(aq) = I2(aq) + 2 KBr(aq)

Ca(OH)2(s) + HCl(aq) = CaCl2(aq) + H2O(l) =>
Ca(OH)2(s) + 2 HCl(aq) = CaCl2(aq) + 2 H2O(l)

CHF4 + H2O = HF + C3H8 + CO2 =>
20 CHF4 + 34 H2O = 80 HF + C3H8 + 17 CO2

NaClO4 + H2O + SO2 = HClO4 + Na2SO3 =>
2 NaClO4 + H2O + SO2 = 2 HClO4 + Na2SO3

H3PO4 + NaCI = Na3PO4 + HCI =>
H3PO4 + 3 NaCI = Na3PO4 + 3 HCI

NaF + I2 = Na2I2 + F2 =>
2 NaF + I2 = Na2I2 + F2

K2Cr2O7 + HCl = KCl + H2O + CrCl2 + Cl2 =>
K2Cr2O7 + 14 HCl = 2 KCl + 7 H2O + 2 CrCl2 + 4 Cl2

C5H14N1 + O2 = CO2 + H2O + N2O3 =>
4 C5H14N1 + 37 O2 = 20 CO2 + 28 H2O + 2 N2O3

HCl + Fe(NO3)3 + KSCN + NaOH = FeCl3 + KNO3 + NaSCN + H2O =>
3 HCl + Fe(NO3)3 + 3 KSCN + 3 NaOH = FeCl3 + 3 KNO3 + 3 NaSCN + 3 H2O

MnO2(S) + H2SO4(l) = Mn(SO4)2(S) + H2O(l) =>
MnO2(S) + 2 H2SO4(l) = Mn(SO4)2(S) + 2 H2O(l)

Na2Co3 + S + SO3 = Na2S2O3 + Co2 =>
2 Na2Co3 + 2 S + 2 SO3 = 2 Na2S2O3 + 3 Co2

1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74
Balance the equation of any chemical reaction
 Equations balanced on the previous day Equations balanced on the next day
Equations balanced on 01/30/25
Equations balanced on 01/07/25
Equations balanced on 02/06/24
Please let us know how we can improve this web app.
Menu Balance Molar mass Gas laws Units Chemistry tools Periodic table Chemical forum Symmetry Constants Contribute Contact us
How to cite?